Personality traits and its relationship with work performance for majority group of farmers in Malaysia - Hassan, Salim; Shayid Khalim Shah, Sarita; Mohamed, Zainal Abidin; Abdullah, Siti Nur Syarafina; Armugam, Kritharan; Wan Matand, Nor Azmiera; Zaini, Nurul Najwa (Australian Academy of Business Leadership, 2016)
Paddy is regarded as the third most widely planted crop in Malaysia that covers an area of 686,050 hectares in total. Although a large scale rice cultivation is practiced in this country, it still falls short in meeting the demand for its ever growing population. According to Rogers’ theory, the majority group (early and late majority) influence most of the paddy production in Malaysia and they form 68% of the paddy farmers. In this regard, it suffices to say that most of the rice supply in this country came from this group of farmers. The objective of the study was to determine the relationship between personality traits and work performance among the paddy farmers in the majority group. A face to face survey was carried out using a questionnaire where the respondents were chosen using the cluster sampling technique. Descriptive analysis was used to describe the demographics of the respondents, while correlation and multiple regressions were used to examine the strength and relationship between personality traits and work performance. The correlation coefficients showed that six personal trait variables were positively correlated with work performance, and only one personal trait variable was negatively correlated with work performance at 0.05 level of significance. Specifically, discipline was found moderately correlated with work performance. Moreover, the results also showed that, the ability to solve problems, network information, and discipline were found to significantly predict work performance of the paddy farmers. Overall, these three variables explained 44% variance of the work performance. Respectively, it is recommended that extension programmes should focus on these three variables in order to increase the work performance of the majority groups of paddy farmers.